Some relations between systems of specific and basic motor dimensions with boxers - Blazevic, S.; Siric, V.; Bilic, Z. (Acta Kinesiologica, 2010)
The sample of respondents in this research presented 92 boxers, age from 22 to 29, Croatian clubs, described with 15 basic motor and 8 specific boxing variable, in order to primarily use cross - correlation analysis and calculate connection between systems of manifest specific and basic motor variables. Then we applied canonical correlation analysis to determine structure of canonical factor and their correlation in order to ,based on this information, enable possibility of forming more rational procedures for their optimal modeling, planning, programming and training control, as well as optimal monitoring of relevant skill development during continuing selection of sportsmen and training process. The results of canonical correlation analysis indicated that relations between canonical factor from specific motor skills variable system, interpreted as integral canonical factor of speed - strength boxer coordination and canonical factor from basic motor skills variable system, interpreted as basic canonical factor of speed - coordination motor skills (conditional, agility), indicates they are statistically significant on the level .00 (p=.00) what completely confirms hypothesis about positive connection of this two areas. Based on obtained research results can be concluded that for deriving variables from the specific motor skill system, optimal motor skill of boxer is needed, based on integrally-interactive base, which completely confirms the assumption it is not possible to develop only one segment of anthropological status and that the other remains intact on such influence. This information can present important factors of transformational processes of programming in boxing, and more specifically that with development of basic motor skills in indirect way relevant boxer`s specific motor dimensions can be developed.